Submucosal administration of onabotulinumtoxinA in the treatment of neurogenic detrusor overactivity: pilot single-centre experience and comparison with standard injection into the detrusor - Šámal, Vladimír; Mečl, Jan; Šrám, Jaroslav (Urologia internationalis, 2013)
INTRODUCTION: Apart from the standard intramural administration of botulinum neurotoxin A (BoNT/A) to the detrusor, intense research is taking place into new means of administration in view of the complex mechanism of action of BoNT/A. METHODS: An open, randomised, prospective study was performed on a total of 23 patients with neurogenic detrusor overactivity. Following randomisation, patients were treated with 300 U of onabotulinumtoxinA (onaBoNT/A) in either the submucosa or the detrusor. Urodynamic examinations were carried out, and a bladder diary was kept both prior to and 12 weeks after the treatment. All patients stopped taking anticholinergics 1 week prior to the treatment. RESULTS: In both the submucosa and detrusor groups, we recorded a significant improvement in the monitored urodynamic parameters and significant decreases in the frequency of urinary incontinence episodes following the treatment. A comparison of the two groups showed no significant difference between the two forms of application, with the exception of voided volume (p = 0.007). CONCLUSION: A comparison of the two administration methods did not show any significant difference between onaBoNT/A administration to the submucosa and to the detrusor. Thus, the submucosal injection of onaBoNT/A represents an equally effective approach for its administration to patients.
Keywords: poranění míchy; injekce intramuskulární; botulotoxiny typu A; endoskopie; výsledek terapie; Middle Aged; urodynamika; mužské pohlaví; Urinary Bladder; Prospective Studies; sliznice; mladý dospělý; močový měchýř; Adult; kvalita života; Injections, Intramuscular; Endoscopy; Muscle, Smooth; Young Adult; neurogenní močový měchýř; ženské pohlaví; Mucous Membrane; Botulinum Toxins, Type A; prospektivní studie; Humans; Urinary Bladder, Neurogenic; inkontinence moči; pilotní projekty; lidé středního věku; Pilot Projects; Urodynamics; Urinary Incontinence; dospělí; Female; Quality of Life; Spinal Cord Injuries; Treatment Outcome; hladké svalstvo; lidé; Male